An Analysis of Modeling Audit Quality Measurement Based on Decision Support Systems (DSS) - Husain, T. (European Journal of Scientific Exploration, 2019)
Many research explicit to the state of difficulty by defining audit quality; they use modeling (theory deployment) from several empirical literature to formulate audit quality in terms of various aspects. The eventful of this research is doing a material or reference for beginner researchers and makes it easy to choose audit quality measurements into the framework that will be applied in his research. The approach used is decision support system (DSS). This type of research is exploratory, using a qualitative approach designed to be able to explain the audit quality measurement model. Data analysis methods adopted by the decision-making / modeling process through three steps i.e. intelligent, design and finally choice phases. The findings of this study show that decision support systems based on structural equation models developed into the audit quality measurement model can be used as recommendations for beginner researchers in formulating definitions, theoretical reviews and measuring audit quality using a specific approach. And the, the goodness-of-fit test in this study can be made recommendations based on each cut-off value criterion in the valuation model in making a fairly fast decision by looking at the output RMSEA score. These testing can be run on statistical software, such as IBM SPSS, AMOS, PLS-Graph, LISREL and others.